Development Of Symphonic Music in Uzbekistan - Professor Sultanali Mannopov; Abdulkhay Karimov; Shohida Ataboeva; Alijon Ergashev; Shokhista Usmanova (Zien Journals, 2021)
This article discusses the entry of symphonic music into the world of Uzbek music and its stages of development. Even today, a number of young composers are working on the development of this genre.
Keywords: Symphony; Symphonic Suite; Overture; Rhapsody